2017
DOI: 10.1186/s40348-017-0071-0
|View full text |Cite
|
Sign up to set email alerts
|

Abstracts of the 52nd Workshop for Pediatric Research

Abstract: /Herdecke University Hospital. Contrary to his brother the boy presented dystrophic at birth (1.715 g birth weight; 150 g below 3rd percentile) and developed adverse gastrointestinal conditions within the first 2 months of life. These included chronic mucosal inflammation and oedematous lamina propria in the intestine, which contributed to intractable diarrhoea. At an age of 7 months the infant eventually died of enteral haemorrhages and liver failure. Further anamnesis revealed several similar fatalities in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Latinopoulos [13] used the basics of the MCDA to develop a MOP (Mathematical Optimization Programming) model that served to efficiently allocate water and land resources in rural Greece. Rozman et al [14] used the DEX method (Decision EXpert) to evaluate dairy farms in Bosnia and Herzegovina. Bogdanović and Hadžić [15] performed a strategic analysis of investments in agriculture using the AHP method and found that perennial plantations are a better long-term investment strategy than conventional crop production.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Latinopoulos [13] used the basics of the MCDA to develop a MOP (Mathematical Optimization Programming) model that served to efficiently allocate water and land resources in rural Greece. Rozman et al [14] used the DEX method (Decision EXpert) to evaluate dairy farms in Bosnia and Herzegovina. Bogdanović and Hadžić [15] performed a strategic analysis of investments in agriculture using the AHP method and found that perennial plantations are a better long-term investment strategy than conventional crop production.…”
Section: Literature Reviewmentioning
confidence: 99%